A composite hemostatic material for quickly controlling non-compressive bleeding and a preparation method thereof

By combining quaternized sodium alginate and aldehyde-modified dextran with 1788 polyvinyl alcohol, a "island structure" with high liquid absorption expansion and mechanical strength is formed, which solves the problem of rapid hemostasis of incompressible bleeding and achieves effective non-compressive bleeding control.

CN119303149BActive Publication Date: 2025-03-25SICHUAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411874018.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and effectively control incompressible bleeding, especially in deep wounds and non-compressive bleeding scenarios, where traditional hemostasis materials have shortcomings in the degree of liquid absorption expansion and mechanical strength.

Method used

The sodium alginate was treated by quaternization, combined with 1788 polyvinyl alcohol and aldehyde-based modified dextran, forming a "island structure" and preparing composite hemostatic material through steps such as foaming, vacuum defoaming and freeze-drying.

Benefits of technology

It achieves rapid blood-sucking dilation, biodegradability and high mechanical strength, significantly improves the hemostasis performance of the composite material, and can effectively control non-compressive bleeding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303149B_ABST
    Figure CN119303149B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hemostatic materials, and provides a composite hemostatic material for quickly controlling non-compressive bleeding and a preparation method thereof; the method comprises: S1 grafting 2,3-epoxypropyltrimethylammonium chloride with sodium alginate to obtain quaternized sodium alginate; S2 dissolving polyvinyl alcohol to obtain a polyvinyl alcohol aqueous solution; S3 performing aldehyde modification on dextran to obtain an aldehyde modified dextran solution; S4 adding the aldehyde modified dextran solution to the polyvinyl alcohol aqueous solution, and then adding quaternized sodium alginate to obtain a mixed solution; S5 foaming, defoaming and freeze drying the mixed solution to obtain an aerogel; S6 washing the aerogel with water and freeze drying to obtain a composite hemostatic material; the invention improves the antibacterial property of sodium alginate by quaternizing the sodium alginate, makes the sodium alginate fully cross-linked with the polyvinyl alcohol as a skeleton structure under the action of the aldehyde modified dextran, and then performs post-treatments such as foaming to improve the porosity and the like, thereby improving the hemostatic property of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hemostatic materials, and in particular relates to a composite hemostatic material for rapidly controlling non-compressive bleeding and a preparation method thereof. Background Art

[0002] Blood is an important means of transport for oxygen and nutrients in the human body. Severe blood loss can cause symptoms of dizziness, shock and organ failure. Bleeding is the main cause of death from traumatic injuries, because massive blood loss often leads to serious complications, including hypotension and multiple organ dysfunction. More than 30% of traumatic deaths worldwide are caused by uncontrolled bleeding, and more than half of deaths occur before the arrival of emergency treatment. Although many reported or sold hemostatic agents have high hemostatic effects on surface bleeding wounds, such as tissue glue, glutaraldehyde cross-linked albumin or gelatin-based hemostatic agents, they are usually not effective for deep wounds caused by small-caliber firearms and improvised explosive devices on the battlefield and in daily life. Because these wounds are usually irregular in shape, what is more challenging is that they are incompressible hemorrhages.

[0003] For incompressible bleeding, gauze and sponges cannot enter the bleeding site, and it is difficult to achieve hemostasis. Conventional powders are difficult to quickly form a stable scab on the wound, and it is usually difficult to stop venous and arterial bleeding. Researchers have developed an expandable hemostat that can be delivered to the internal bleeding site, absorb blood and then expand to stop bleeding. Although new hemostatic drugs show good hemostatic effects in the hemostasis of non-compressible bleeding, there are still limitations. The X-type rapid hemostatic system (XStat™) containing a large amount of compressed cellulose sponge has strong adhesion and is not biodegradable. Potential residues after surgery may cause postoperative damage and even require a second surgical resection. Many shape memory polymer hemostats have limited absorption of blood, poor anti-extrusion strength, and require more than ten seconds or even tens of seconds or longer to restore their shape. These hemostats often prolong the hemostasis time and may cause increased blood loss. Chinese patent CN115300665A discloses an antibacterial absorbable nasal hemostatic sponge, which contains the following components in mass proportion: gelatin, chitosan, polyvinyl alcohol, sodium alginate, polylactic acid, and cross-linking agent in a mass fraction ratio of 2: (1-2): 1: 1: 2: (0.003-0.005). However, the polyvinyl alcohol and sodium alginate of the antibacterial absorbable nasal hemostatic sponge are mixed, and a separate elastomeric material needs to be used. Therefore, the development of a composite hemostatic material with rapid blood absorption and expansion, biodegradability, and for rapid control of fatal non-compressible and non-compressive bleeding is highly anticipated, and this remains an ongoing challenge. Summary of the invention

[0004] In response to the problem of how to quickly stop the above-mentioned incompressible bleeding, the present invention provides a composite hemostatic material for quickly controlling non-compressible bleeding and a preparation method, aiming to prepare a hemostatic material with rapid blood absorption and expansion, biodegradability and for non-compressible bleeding.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a composite hemostatic material for rapidly controlling non-compressive bleeding, characterized in that it comprises the following steps:

[0007] S1, mixing sodium alginate, 2,3-epoxypropyltrimethylammonium chloride and deionized water to perform a quaternization reaction, and then adjusting the pH to obtain quaternized sodium alginate;

[0008] S2, dissolving 1788 type polyvinyl alcohol in deionized water, and then heating and stirring to obtain 1788 type polyvinyl alcohol aqueous solution;

[0009] S3, acidifying the dextran aqueous solution, and then adding an aldehyde-modifying agent to carry out a modification reaction to obtain an aldehyde-modified dextran solution;

[0010] S4, adding the aldehyde-modified dextran solution to the 1788-type polyvinyl alcohol aqueous solution, and then adding quaternized sodium alginate to obtain a mixed solution;

[0011] S5, stirring and foaming, vacuum degassing and freeze-drying the mixed solution in sequence to obtain freeze-dried aerogel;

[0012] S6. Washing the freeze-dried aerogel, adjusting the pH, and freeze-drying the aerogel in sequence to obtain a composite hemostatic material.

[0013] The preparation mechanism and beneficial effects of the present invention are:

[0014] By using 2,3-epoxypropyltrimethylammonium chloride as a quaternary ammonium agent and then introducing cationic groups to modify sodium alginate, the cations it carries can interact with the negatively charged bacterial wall, thereby making the modified quaternized sodium alginate have antibacterial properties.

[0015] By dissolving 1788 polyvinyl alcohol in water, the hydrogen bonds between the 1788 polyvinyl alcohol molecules can be destroyed, and the polyvinyl alcohol can be fully dissolved to facilitate subsequent mixing and reaction with other materials;

[0016] By acidifying the aqueous solution of dextran and adding an aldehyde modifier, a macromolecular polysaccharide structure containing multiple aldehyde groups can be obtained as a cross-linking agent. The high aldehyde group density of its molecular chain can not only form a local high-density cross-linked network system with the matrix, but the macromolecular structure of the cross-linking agent can also span multiple cross-linked network regions, thereby improving the stability between the cross-linked networks, and forming a stable interconnected island structure as a whole. The double cross-linked network system of the island structure can give the composite material high mechanical strength, good liquid absorption and expansion, and excellent hemostatic properties.

[0017] In the stirring and foaming step in step S5, hydrochloric acid is specifically used as an acidic catalyst. After the system is allowed to stand to room temperature, the acidic catalyst is added under stirring, and then the foaming reaction is fully stirred. The addition of the acidic catalyst promotes the formation of hemiacetal bonds between the hydroxyl groups of 1788 polyvinyl alcohol and quaternized sodium alginate and the active aldehyde groups of the cross-linking agent. Due to the water solvent of the system and the macromolecular structure of the cross-linking agent, the reaction proceeds slowly and the viscosity of the system is high, so that the system is foamed by sufficient stirring and the porosity of the final material is improved.

[0018] By adopting vacuum degassing, uneven large bubbles in the stirring process can be removed, thereby avoiding the undesirable situation in which the system structure is destroyed due to uneven pore size of the system, affecting the liquid absorption performance of the composite material, reducing the mechanical strength of the material, and reducing the hemostatic efficiency.

[0019] In summary, the present invention improves the antibacterial properties of sodium alginate by quaternizing it, so that it is fully cross-linked with 1788 type polyvinyl alcohol as a skeleton structure under the action of the cross-linking agent aldehyde-modified dextran to form an "island structure", and combines post-treatments such as foaming, vacuum degassing, and freeze-drying to further improve the porosity, pore size and mechanical strength, thereby improving the hemostatic performance of the composite material.

[0020] Furthermore, in step S1, the mass ratio of the sodium alginate to the 2,3-epoxypropyltrimethylammonium chloride is (2-8):(3-8).

[0021] Furthermore, in step S3, the mass ratio of the dextran to the glutaraldehyde is (0.5-3.5):(0.5-1.6).

[0022] Furthermore, in step S1, the pH value is ≤7.

[0023] In the present invention, in step S1, after the pH value is adjusted, an excess of ethanol is used for precipitation, the product is collected and dried, and finally quaternized sodium alginate is obtained.

[0024] Furthermore, in step S6, the pH value is 7-8.

[0025] In the present invention, a sodium bicarbonate solution with a mass fraction of 7.75% is used to adjust the pH value in step S6, thereby removing the acidic catalyst in the original system and preventing the acidic impurities in the material from affecting the hemostatic performance of the material.

[0026] Furthermore, in step S3, the molecular weight of glucose in the dextran aqueous solution is 60,000-80,000.

[0027] In the present invention, the molecular weight of aldehyde-modified dextran is controlled by adjusting the molecular weight of glucose, thereby controlling the cross-linked network system of the system, thereby controlling the porosity, pore size and mechanical properties of the material, and finally obtaining a composite material with optimal hemostatic performance.

[0028] Furthermore, the modifier comprises at least one of glutaraldehyde and glyoxal.

[0029] Furthermore, in step S3, the acidification treatment uses hydrochloric acid with a mass fraction of 3.3%.

[0030] Furthermore, in step S5, the first stage treatment temperature of the vacuum degassing is -35 to -20°C, and the treatment time is 2 to 4 hours; the second stage treatment temperature is -50°C to 0°C, and the treatment time is 24 to 48 hours.

[0031] By adjusting the pre-freezing (first stage processing temperature) and freezing (second stage processing temperature) drying temperatures, the size and number of ice crystals in the system can be effectively adjusted, thereby adjusting the porosity and pore size of the composite material. The cross-linking reaction of the composite material occurs during the freeze-drying dehydration process, at which time the shape and structure of the system are basically fixed, which is conducive to the customized regulation of porosity and pore size.

[0032] The second object of the present invention is to provide a composite hemostatic material obtained by any one of the preparation methods described above:

[0033] The composite hemostatic material is composed of the following chemical components in parts by weight: 1 to 10 parts of quaternized sodium alginate, 10 to 15 parts of 1788 type polyvinyl alcohol, and 0.1 to 5 parts of aldehyde-modified dextran.

[0034] The technical mechanism and beneficial effects of the present invention are:

[0035] The present invention uses 1788-type polyvinyl alcohol and quaternized sodium alginate as matrix materials; wherein, 1788-type polyvinyl alcohol serves as the skeleton structure of the composite material, giving the material good mechanical properties, and playing the role of supporting the intelligent hemostasis of the wound; and quaternized sodium alginate has excellent biocompatibility, can promote wound healing and hemostasis, and can be adjusted with 1788-type polyvinyl alcohol in a mutually adjusted ratio to prepare a composite hemostatic material, which can play the role of supporting the wound and assisting hemostasis, and will not cause secondary damage to the wound due to excessive mechanical strength;

[0036] Furthermore, the present invention abandons traditional small molecule cross-linking agents and selects modified polyaldehyde polysaccharide cross-linking agents. While forming a local high-density cross-linking network system, the cross-linking agent macromolecular structure can span multiple cross-linking network regions, thereby improving the stability between the cross-linking networks. The material as a whole forms a stably interconnected island structure, which gives the composite material high mechanical strength, good liquid absorption and swelling, and excellent hemostatic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0038] Figure 1 Micro-CT simulated 3D structural images of the initial freeze-dried sample (a, c) and the secondary freeze-dried sample (b, d) after washing of the composite hemostatic material provided in Example 1 of the present application;

[0039] Figure 2 Schematic diagram of the composite hemostatic material provided in Example 1 of the present application in the initial state (a), compression (b) and liquid absorption and re-expansion (c) simulation test;

[0040] Figure 3 SEM images of the composite hemostatic material provided in Example 1 of the present application in the initial state a (500 μm), d (20 μm), compression b (500 μm), e (20 μm) and liquid absorption and re-expansion c (500 μm), f (20 μm) simulation test. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0042] Example 1

[0043] This embodiment provides a composite hemostatic material for quickly controlling non-compressive bleeding, and a preparation method thereof, specifically comprising the following steps:

[0044] (1) Use polyvinyl alcohol type 1788 (BiDe Pharmaceutical, purity 1788), sodium alginate (Shanghai Aladdin Biochemical Technology Co., Ltd., viscosity 200±20 mPa·s), 2,3-epoxypropyltrimethylammonium chloride (Shanghai Aladdin Biochemical Technology Co., Ltd., ≥95%), dextran (Shanghai MacLean Biochemical Technology Co., Ltd., molecular weight 70000), glutaraldehyde 50% (Chengdu Kelong Chemical Co., Ltd., analytical grade), hydrochloric acid (Chengdu Kelong Chemical Co., Ltd., purity 20%), sodium bicarbonate (Shanghai Aladdin Biochemical Technology Co., Ltd., AR, ≥99.8%);

[0045] (2) Weighing and preparing the raw materials, the weight ratio of the raw materials is: the weight ratio of 1788 polyvinyl alcohol, sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, dextran, glutaraldehyde, hydrochloric acid, and sodium bicarbonate solution is 10:3:5.145:0.672:1.6:5:3;

[0046] (3) Dissolve sodium alginate in deionized water and stir thoroughly until completely dissolved, add 2,3-epoxypropyltrimethylammonium chloride and stir thoroughly, and place the reaction in a stirrer at 60°C, away from light for 24 hours;

[0047] (4) Adjust the pH value to below 7 and then place at room temperature. Add excess ethanol for precipitation, collect the product and dry it to obtain quaternized sodium alginate;

[0048] (5) Dissolve 1788 polyvinyl alcohol in deionized water and stir at 90 °C at 1200 rpm for 2 hours;

[0049] (6) Take 8.25 ml of hydrochloric acid and add it to a 50 ml volumetric flask. Add deionized water to dilute it to obtain a hydrochloric acid with a mass fraction of 3.3%;

[0050] (7) dissolving dextran in deionized water, adding hydrochloric acid to acidify, adding glutaraldehyde solution to stir and react to obtain glutaraldehyde-modified dextran;

[0051] (8) Mix the 1788 polyvinyl alcohol solution and the polyaldehyde dextran solution, and stir at 50°C to mix well;

[0052] (9) Under stirring conditions, add quaternized sodium alginate to the solution (8), and stir at 50° C. at a speed of 1200 rpm for 1 hour;

[0053] (10) Pour the mixed solution into a beaker and let it stand at room temperature, then gradually add hydrochloric acid to acidify it, and stir and foam it at a speed of 1800 rpm for 1.5 hours;

[0054] (11) pouring the foam solution into a mold, vacuum degassing, pre-freezing at -35 °C for 4 hours, and then freeze-drying the sample at -50 °C for 48 hours to obtain freeze-dried aerogel;

[0055] (12) Take 4 g of sodium bicarbonate, dissolve it in deionized water, pour it into a 50 ml volumetric flask and dilute it to prepare a sodium bicarbonate solution with a mass fraction of 7.75%;

[0056] (13) The freeze-dried aerogel in (11) was rinsed in deionized water for 1 hour, sodium bicarbonate solution was added to adjust the solution pH to 7-8, and then pre-frozen at -35°C for 4 hours. The sample was freeze-dried at -50°C for 24 hours to finally obtain a composite hemostatic material for rapid control of non-compressive bleeding.

[0057] The microstructure of the material was characterized by scanning electron microscopy (SEM). The microscopic average pore diameter of the material was measured using ImageJ software (version: 1.53k). The porosity of the material was determined in accordance with the national standard GB / T 33052-2016, and the liquid replacement method was used to determine its porosity.

[0058] One of the key factors affecting the hemostatic performance of materials is the hydrophilicity of the hemostatic material. The water contact angle is a suitable parameter for determining the hydrophilicity of all trimmed surfaces. The composite hemostatic material prepared by the present invention has good hydrophilicity and a complex pore structure. In order to better reflect the hydrophilicity of the material, the present invention uses a contact angle analyzer (Data physics Instruments, DSA30, Germany) to measure the residence time of a 4 μL droplet on the surface of the composite hemostatic material and the contact angle between the droplet and the sponge when the droplet stays on the surface of the composite hemostatic material for 3 s. The liquid absorption rate and liquid absorption swelling degree test of the composite hemostatic material refer to the pharmaceutical industry standard YY / T 1803-2021 standard. A piece of composite hemostatic material is immersed in a PBS solution until the sponge is soaked with liquid. The liquid absorption capacity and liquid absorption swelling degree of the sponge are obtained by weight and volume changes.

[0059] The mechanical strength and fatigue resistance of the composite hemostatic material after swelling after absorbing liquid are important factors in providing a stable physical hemostatic barrier. The composite hemostatic material was subjected to stress-strain tests using the CMT4104 universal testing machine of Shenzhen Xinsansi Material Testing Co., Ltd. The material was compressed to 85% strain at a rate of 5 mm / s in each cycle, and recovered at the same speed, and repeated five times.

[0060] The hemostatic effect of the composite hemostatic material was evaluated using the rat liver cross incision hemostasis model, the rat liver standard disc loss hemostasis model, and the rat femoral artery transverse incision hemostasis model. The composite hemostatic material slices (5 mm thick, 15 mm side length) were sterilized by ultraviolet irradiation for 1 hour. Rats were anesthetized by intraperitoneal injection of 10% chloral hydrate and fixed on a board. All animal experiments were performed in strict accordance with the guidelines for the care and use of laboratory animals of the National Institutes of Health (NIH).

[0061] After testing, the average pore diameter of the material was 29.8 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 3 s, and the contact angle of the material was 0° at three seconds. The porosity of the composite hemostatic material was 84.17%, the liquid absorption rate was 3590%, the liquid absorption expansion was 8046%, and the compressive strength was 166.23 Kpa. The blood loss of the composite hemostatic material in the rat liver cross incision hemostasis model, the rat liver standard disc loss hemostasis model, and the rat femoral artery transverse incision hemostasis model were 0.32 g, 0.6 g, and 1.1 g, respectively.

[0062] according to Figure 1 The Micro-CT simulated 3D structure restoration diagram of the initial freeze-dried sample (a, c) and the second freeze-dried sample after washing (b, d) of the composite hemostatic material shows that the porosity of the second freeze-dried sample after washing is significantly increased and the density is significantly reduced. Figure 2 The schematic diagrams of the composite hemostatic material in the initial state (a), compression (b) and liquid absorption and re-expansion (c) simulation test show that the composite hemostatic material can recover its original state and have a certain degree of expansion after absorbing water again after compression. Figure 3 From the SEM images of the composite hemostatic material in the simulation tests of initial state a (500μm), d (20μm), compression b (500μm), e (20μm) and liquid absorption and expansion c (500μm), f (20μm), it can be seen that in the SEM images, the pore structure of the composite hemostatic material remains intact and is not obviously damaged after compression and liquid absorption and expansion.

[0063] Example 2

[0064] The difference between this embodiment and embodiment 1 is that the weight ratio of the prepared materials is: the weight ratio of 1788 type polyvinyl alcohol, sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, dextran, glutaraldehyde, hydrochloric acid, and sodium bicarbonate solution is 10:3:5.145:0.51:1:5:3.

[0065] After testing, the average pore diameter of the material was 40.0 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 4.3 s, and the contact angle of the material was 55.78° at three seconds. The porosity of the composite hemostatic material was 87.58%, the liquid absorption rate was 3758%, the liquid absorption swelling degree was 973.6%, and the compressive strength was 157.14 Kpa. The blood loss of the composite hemostatic material in the rat liver cross incision hemostasis model, the rat liver standard disc loss hemostasis model, and the rat femoral artery transverse incision hemostasis model were 0.5 g, 0.6 g, and 1.1 g, respectively.

[0066] It can be seen that in Example 1, by increasing the amount of aldehyde-deoxyglucan cross-linking agent, the anti-extrusion performance and hemostatic performance of the material after liquid absorption and swelling are significantly improved. The main purpose of increasing the amount of aldehyde-deoxyglucan cross-linking agent is to improve the mechanical properties of the material, and the hydrophilicity of the material is also significantly improved. Although the liquid absorption rate and liquid absorption swelling degree of the material in Example 1 are reduced, its hemostatic performance is significantly improved, indicating that the surface hydrophilicity of the composite hemostatic material has a greater influence on the hemostatic performance of the material than the porosity and liquid absorption rate.

[0067] Example 3

[0068] The difference between this embodiment and embodiment 1 is that the weight ratio of the prepared materials is: the weight ratio of 1788 type polyvinyl alcohol, sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, dextran, glutaraldehyde, hydrochloric acid, and sodium bicarbonate solution is 15:2.3:3.94:1.01:2.4:5:3.

[0069] After testing, at a scale of 500 μm, the average pore diameter of the material is 27.64 μm. The porosity of the composite hemostatic material is 77.95%, the liquid absorption rate is 1396%, the liquid absorption expansion is 5626%, and the compressive strength is 222.69 Kpa.

[0070] It can be seen that in Example 1, by reducing the amount of 1788 polyvinyl alcohol, the liquid absorption rate and liquid swelling degree of the material are significantly improved. The main purpose of adding 1788 polyvinyl alcohol is to improve the porosity and mechanical properties of the material, but too much addition of 1788 polyvinyl alcohol will reduce the hydrophilicity of the material, and too high mechanical properties will also cause secondary damage to the wound.

[0071] Example 4

[0072] The difference between this embodiment and embodiment 1 is that 40% glyoxal (Bi De Pharmaceutical, analytical grade) is selected as the aldehyde modifier of dextran, and the weight ratio of the prepared materials is: the weight ratio of 1788 type polyvinyl alcohol, sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, dextran, glyoxal, hydrochloric acid, and sodium bicarbonate solution is 10:3:5.145:0.672:1.6:5:3.

[0073] After testing, the average pore diameter of the material was 27.9 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 3 s, and the contact angle of the material was 0° at three seconds. The porosity of the composite hemostatic material was 88.72%, the liquid absorption rate was 3660%, the liquid absorption expansion was 7880%, and the compressive strength was 151.12 Kpa. The blood loss of the composite hemostatic material in the rat liver cross incision hemostasis model, the rat liver standard disc loss hemostasis model, and the rat femoral artery transverse incision hemostasis model were 0.28 g, 0.55 g, and 1.05 g, respectively. It can be seen that glyoxal and glutaraldehyde can both be used as aldehyde modifiers for dextran.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 1 is that the cross-linking agent is glutaraldehyde.

[0076] This comparative example provides a composite hemostatic material for quickly controlling non-compressive bleeding, and its preparation method specifically comprises the following steps:

[0077] (1) Use 1788 type polyvinyl alcohol (BiDe Pharmaceutical, purity 1788), sodium alginate (Shanghai Aladdin Biochemical Technology Co., Ltd., viscosity 200±20 mPa·s), 2,3-epoxypropyltrimethylammonium chloride (Shanghai Aladdin Biochemical Technology Co., Ltd., ≥95%), glutaraldehyde 50% (Chengdu Kelong Chemical Co., Ltd., analytical grade), hydrochloric acid (Chengdu Kelong Chemical Co., Ltd., purity 20%), sodium bicarbonate (Shanghai Aladdin Biochemical Technology Co., Ltd., AR, ≥99.8%);

[0078] (2) Weighing and preparing the raw materials, the weight ratio of the raw materials is: the weight ratio of 1788 polyvinyl alcohol, sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, glutaraldehyde, hydrochloric acid, and sodium bicarbonate solution is 10:3:5.145:1.6:5:3;

[0079] (3) Dissolve sodium alginate in deionized water and stir thoroughly until completely dissolved, add 2,3-epoxypropyltrimethylammonium chloride and stir thoroughly, and place the reaction in a stirrer at 60°C, away from light for 24 hours;

[0080] (4) Adjust the pH value to below 7 and then place at room temperature. Add excess ethanol for precipitation, collect the product and dry it to obtain quaternized sodium alginate;

[0081] (5) Dissolve 1788 polyvinyl alcohol in deionized water and stir at 90 °C at 1200 rpm for 2 hours;

[0082] (6) Under stirring conditions, quaternized sodium alginate was added to the solution, and the mixture was stirred at 50° C. at a speed of 1200 rpm for 1 hour;

[0083] (7) Take 8.25 ml of hydrochloric acid and add it to a 50 ml volumetric flask. Add deionized water to dilute it to obtain a hydrochloric acid with a mass fraction of 3.3%.

[0084] (8) Pour the mixed solution into a beaker and let it stand at room temperature, then gradually add hydrochloric acid to acidify it, and stir and foam it at a speed of 1800 rpm for 1.5 hours;

[0085] (9) Add glutaraldehyde solution and stir thoroughly;

[0086] (10) The foam solution was poured into a mold, and the material was quickly formed. After pre-freezing at -35 °C for 4 hours, the sample was freeze-dried at -50 °C for 48 hours to obtain an aerogel;

[0087] (11) Take 4 g of sodium bicarbonate, dissolve it in deionized water, pour it into a 50 ml volumetric flask and dilute it to prepare a sodium bicarbonate solution with a mass fraction of 7.75%;

[0088] (12) The aerogel was rinsed in deionized water for 1 hour, and sodium bicarbonate solution was added to adjust the solution pH to 7-8. The solution was pre-frozen at -35 °C for 4 hours, and the sample was freeze-dried at -50 °C for 24 hours to finally obtain a composite hemostatic material.

[0089] After testing, the average pore diameter of the material was 70.6 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 6.3 s, and the contact angle of the material was 59.7° at three seconds. The porosity of the composite hemostatic material was 73.27%, the liquid absorption rate was 2210%, the liquid absorption swelling degree was 439.9%, and the compressive strength was 88.56 Kpa. The blood loss of the composite hemostatic material in the rat liver cross incision hemostasis model, the rat liver standard disc loss hemostasis model, and the rat femoral artery transverse incision hemostasis model were 0.4 g, 0.8 g, and 1.9 g, respectively.

[0090] It can be seen that in Example 1, by replacing the cross-linking agent from small molecule glutaraldehyde with aldehyde-deoxyglucan cross-linking agent, the anti-extrusion performance, water contact angle and hemostatic performance of the material after liquid absorption and swelling are significantly improved. The main purpose of replacing the cross-linking agent with aldehyde-deoxyglucan is to improve the mechanical properties of the material, but it is unexpected that the liquid absorption and swelling degree of the material is also significantly improved.

[0091] Comparative Example 2

[0092] The difference between this comparative example and Example 1 is that the composite hemostatic material does not contain glutaraldehyde-modified dextran cross-linking agent.

[0093] This comparative example provides a composite hemostatic material for quickly controlling non-compressive bleeding, and its preparation method specifically comprises the following steps:

[0094] (1) Use 1788 polyvinyl alcohol (BiDe Pharmaceutical, purity 1788), sodium alginate (Shanghai Aladdin Biochemical Technology Co., Ltd., viscosity 200±20 mPa·s), 2,3-epoxypropyltrimethylammonium chloride (Shanghai Aladdin Biochemical Technology Co., Ltd., ≥95%), hydrochloric acid (Chengdu Kelong Chemical Co., Ltd., purity 20%), sodium bicarbonate (Shanghai Aladdin Biochemical Technology Co., Ltd., AR, ≥99.8%);

[0095] (2) Weighing and preparing the raw materials, the weight ratio of the raw materials is: the weight ratio of 1788 polyvinyl alcohol, sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, hydrochloric acid, and sodium bicarbonate solution is 10:4.7:8.06:5:3;

[0096] (3) Dissolve sodium alginate in deionized water and stir thoroughly until completely dissolved, add 2,3-epoxypropyltrimethylammonium chloride and stir thoroughly, and place the reaction in a stirrer at 60°C, away from light for 24 hours;

[0097] (4) Adjust the pH value to below 7 and then place at room temperature. Add excess ethanol for precipitation, collect the product and dry it to obtain quaternized sodium alginate;

[0098] (5) Dissolve 1788 polyvinyl alcohol in deionized water and stir at 90 °C at 1200 rpm for 2 hours;

[0099] (6) Under stirring conditions, quaternized sodium alginate was added to the solution and stirred at 50 °C at a speed of 1200 rpm for 1 hour;

[0100] (7) Take 8.25 ml of hydrochloric acid and add it to a 50 ml volumetric flask. Add deionized water to dilute it to obtain a hydrochloric acid with a mass fraction of 3.3%.

[0101] (8) Pour the mixed solution into a beaker and let it stand at room temperature, then gradually add hydrochloric acid to acidify it, and stir and foam it at a speed of 1800 rpm for 1.5 hours;

[0102] (9) The foam solution was poured into a mold and vacuum-degassed. After pre-freezing at -35°C for 4 hours, the sample was freeze-dried at -50°C for 48 hours to obtain a composite hemostatic material.

[0103] After testing, at a scale of 500 μm, the average pore diameter of the material is 42.1 μm. The residence time of the droplet on the surface of the composite hemostatic material is 57.3 s, and the contact angle of the material is 103.77° at three seconds. The porosity of the composite hemostatic material is 72.47%, and the liquid absorption rate is 1011.2%. After the composite hemostatic material of Comparative Example 2 absorbs water, its structure collapses, and the liquid absorption expansion and compression strength cannot be measured.

[0104] It can be seen that in Example 1 of the present application, by adding the formaldehyde-deoxyglucan cross-linking agent, the anti-extrusion performance, hydrophilicity, and liquid absorption rate of the material after liquid absorption and swelling are significantly improved. The main purpose of adding the formaldehyde-deoxyglucan cross-linking agent is to improve the mechanical properties of the material, but it is unexpected that the liquid absorption and swelling degree of the material is also significantly improved.

[0105] Comparative Example 3

[0106] The difference between this comparative example and Example 1 is that the composite hemostatic material contains sodium alginate.

[0107] This comparative example provides a composite hemostatic material for quickly controlling non-compressive bleeding, and its preparation method specifically comprises the following steps:

[0108] (1) Use polyvinyl alcohol type 1788 (BiDe Pharmaceutical, purity 1788), sodium alginate (Shanghai Aladdin Biochemical Technology Co., Ltd., viscosity 200±20 mPa·s), dextran (Shanghai McLean Biochemical Technology Co., Ltd., molecular weight 70000), glutaraldehyde 50% (Chengdu Kelong Chemical Co., Ltd., analytical grade), hydrochloric acid (Chengdu Kelong Chemical Co., Ltd., purity 20%), sodium bicarbonate (Shanghai Aladdin Biochemical Technology Co., Ltd., AR, ≥99.8%);

[0109] (2) Weighing and preparing the raw materials, the weight ratio of the raw materials is: the weight ratio of 1788 polyvinyl alcohol, sodium alginate, dextran, glutaraldehyde, hydrochloric acid, and sodium bicarbonate solution is 10:3:0.672:1.6:5:3;

[0110] (3) Dissolve 1788 polyvinyl alcohol in deionized water and stir at 90 °C at a speed of 1200 rpm for 2 hours;

[0111] (4) Take 8.25 ml of hydrochloric acid and add it to a 50 ml volumetric flask. Add deionized water to dilute it to obtain a hydrochloric acid with a mass fraction of 3.3%;

[0112] (5) dissolving dextran in deionized water, adding hydrochloric acid to acidify, adding glutaraldehyde solution to stir and react to obtain glutaraldehyde-modified dextran;

[0113] (6) Mix the 1788 polyvinyl alcohol solution and the polyaldehyde dextran solution, and stir at 50°C to mix well;

[0114] (7) Under stirring conditions, sodium alginate was added to the solution (6), and the mixture was stirred at 50° C. at a speed of 1200 rpm for 1 hour;

[0115] (8) Pour the mixed solution into a beaker and let it stand at room temperature, then gradually add hydrochloric acid to acidify it, and stir and foam it at a speed of 1800 rpm for 1.5 hours;

[0116] (9) Pour the foam solution into a mold, vacuum degas, pre-freeze at -35°C for 4 hours, and then freeze-dry the sample at -50°C for 48 hours;

[0117] (10) Take 4 g of sodium bicarbonate, dissolve it in deionized water, pour it into a 50 ml volumetric flask and dilute it to prepare a sodium bicarbonate solution with a mass fraction of 7.75%;

[0118] (11) The freeze-dried aerogel prepared in (9) was rinsed in deionized water for 1 hour, and sodium bicarbonate solution was added to adjust the solution pH to 7-8, and then the solution was pre-frozen at -35°C for 4 hours. The sample was freeze-dried at -50°C for 24 hours to finally obtain a composite hemostatic material for rapid control of non-compressive bleeding.

[0119] After testing, the average pore diameter of the material was 31.2 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 3 s, and the contact angle of the material was 0° at three seconds. The porosity of the composite hemostatic material was 80.1%, the liquid absorption rate was 3510%, the liquid absorption expansion was 7840%, and the compressive strength was 140.12 Kpa. The blood loss of the composite hemostatic material in the rat liver cross incision hemostasis model, the rat liver standard disc loss hemostasis model, and the rat femoral artery transverse incision hemostasis model were 0.5 g, 0.8 g, and 1.6 g, respectively.

[0120] It can be seen that in Example 1 of the present application, the grafting of quaternary ammonium groups onto sodium alginate has little effect on the material's hydrophilicity and liquid absorption rate, but the material's hemostatic properties are greatly improved. Quaternary ammonium sodium alginate carries a positive charge that can promote red blood cell aggregation, thereby promoting wound coagulation.

[0121] Comparative Example 4

[0122] The difference between this comparative example and Example 1 is that the base material of the hemostatic material is only quaternized sodium alginate.

[0123] This comparative example provides a composite hemostatic material for quickly controlling non-compressive bleeding, and its preparation method specifically comprises the following steps:

[0124] (1) Sodium alginate (Shanghai Aladdin Biochemical Technology Co., Ltd., viscosity 200±20 mPa·s), 2,3-epoxypropyltrimethylammonium chloride (Shanghai Aladdin Biochemical Technology Co., Ltd., ≥95%), dextran (Shanghai MacLean Biochemical Technology Co., Ltd., molecular weight 70000), glutaraldehyde 50% (Chengdu Kelong Chemical Co., Ltd., analytical grade), hydrochloric acid (Chengdu Kelong Chemical Co., Ltd., purity 20%), sodium bicarbonate (Shanghai Aladdin Biochemical Technology Co., Ltd., AR, ≥99.8%);

[0125] (2) Weighing and preparing the raw materials, the weight ratio of the raw materials is: sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, dextran, glutaraldehyde, hydrochloric acid, and sodium bicarbonate solution is 3:5.145:0.336:0.8:5:3;

[0126] (3) Dissolve sodium alginate in deionized water and stir thoroughly until completely dissolved, add 2,3-epoxypropyltrimethylammonium chloride and stir thoroughly, and place the reaction in a stirrer at 60°C, away from light for 24 hours;

[0127] (4) Adjust the pH value to below 7 and then place at room temperature. Add excess ethanol for precipitation, collect the product and dry it to obtain quaternized sodium alginate;

[0128] (5) Dissolve quaternized sodium alginate in deionized water and stir at 1200 rpm at 50 °C for 1 hour;

[0129] (6) Take 8.25 ml of hydrochloric acid and add it to a 50 ml volumetric flask. Add deionized water to dilute it to obtain a hydrochloric acid with a mass fraction of 3.3%;

[0130] (7) dissolving dextran in deionized water, adding hydrochloric acid to acidify, adding glutaraldehyde solution to stir and react to obtain glutaraldehyde-modified dextran;

[0131] (8) Mix the quaternized sodium alginate solution and the polyaldehyde dextran solution and stir at 50 °C for 0.5 h;

[0132] (9) Pour the mixed solution into a beaker and let it stand at room temperature, then gradually add hydrochloric acid to acidify it, and stir and foam it at 1800 rpm for 1.5 hours;

[0133] (10) The foam solution was poured into a mold, vacuum-degassed, and pre-frozen at -35 °C for 4 hours. The sample was then freeze-dried at -50 °C for 48 hours.

[0134] (11) Take 4 g of sodium bicarbonate, dissolve it in deionized water, pour it into a 50 ml volumetric flask and dilute it to prepare a sodium bicarbonate solution with a mass fraction of 7.75%;

[0135] (12) The freeze-dried aerogel in (10) was rinsed in deionized water for 1 hour, sodium bicarbonate solution was added to adjust the solution pH to 7-8, and then pre-frozen at -35°C for 4 hours. The sample was freeze-dried at -50°C for 24 hours to finally obtain a composite hemostatic material for rapid control of non-compressive bleeding.

[0136] After testing, the average pore diameter of the material was 20.5 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 8 s, and the contact angle of the material was 53.2° at three seconds. The porosity of the composite hemostatic material was 70.1%, the liquid absorption rate was 1510%, and the liquid absorption swelling degree was 840%.

[0137] It can be seen that Example 1 of the present application selects quaternized sodium alginate and 1788-type polyvinyl alcohol to form a composite hemostatic material, which gives the material high porosity, high surface area and pore volume. When the matrix is ​​only quaternized sodium alginate, the hemostatic material collapses after absorbing liquid, indicating that 1788-type polyvinyl alcohol as a skeleton structure can give the material good mechanical properties and play a role in supporting the intelligent hemostasis of wounds.

[0138] Comparative Example 5

[0139] The difference between this comparative example and Example 1 is that the hemostatic material matrix is ​​only 1788 type polyvinyl alcohol.

[0140] (1) Use polyvinyl alcohol type 1788 (BiDe Pharmaceutical, purity 1788), dextran (Shanghai McLean Biochemical Technology Co., Ltd., molecular weight 70,000), glutaraldehyde 50% (Chengdu Kelong Chemical Co., Ltd., analytical grade), hydrochloric acid (Chengdu Kelong Chemical Co., Ltd., purity 20%), and sodium bicarbonate (Shanghai Aladdin Biochemical Technology Co., Ltd., AR, ≥99.8%);

[0141] (2) Weighing and preparing the raw materials, the weight ratio of the raw materials is: the weight ratio of 1788 polyvinyl alcohol, dextran, glutaraldehyde, hydrochloric acid, and sodium bicarbonate solution is 10: 0.336: 0.8: 5: 3;

[0142] (3) Dissolve 1788 polyvinyl alcohol in deionized water and stir at 90 °C at a speed of 1200 rpm for 2 hours;

[0143] (4) Take 8.25 ml of hydrochloric acid and add it to a 50 ml volumetric flask. Add deionized water to dilute it to obtain a hydrochloric acid with a mass fraction of 3.3%;

[0144] (5) dissolving dextran in deionized water, adding hydrochloric acid to acidify, adding glutaraldehyde solution to stir and react to obtain glutaraldehyde-modified dextran;

[0145] (6) Mix the 1788 polyvinyl alcohol solution and the polyaldehyde dextran solution, and stir at 50°C for 0.5 h;

[0146] (7) Pour the mixed solution into a beaker and let it stand at room temperature, then gradually add hydrochloric acid to acidify it, and stir and foam it at 1800 rpm for 1.5 hours;

[0147] (8) Pour the foam solution into a mold, vacuum degas, pre-freeze at -35°C for 4 hours, and then freeze-dry the sample at -50°C for 48 hours;

[0148] (9) Take 4 g of sodium bicarbonate, dissolve it in deionized water, pour it into a 50 ml volumetric flask and dilute it to prepare a sodium bicarbonate solution with a mass fraction of 7.75%;

[0149] (10) The freeze-dried aerogel in (8) was rinsed in deionized water for 1 hour, sodium bicarbonate solution was added to adjust the solution pH to 7-8, and then pre-frozen at -35°C for 4 hours. The sample was freeze-dried at -50°C for 24 hours to finally obtain a composite hemostatic material for rapid control of non-compressive bleeding.

[0150] After testing, the average pore diameter of the material was 45.1 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 60 s, and the contact angle of the material was 62.2° at three seconds. The porosity of the composite hemostatic material was 80.1%, the liquid absorption rate was 612%, and the liquid absorption swelling degree was 125%.

[0151] It can be seen that Example 1 of the present application selects quaternized sodium alginate and 1788-type polyvinyl alcohol to form a composite hemostatic material, which gives the material a flexible structure, high hydrophilicity and efficient hemostatic performance. When the matrix is ​​only 1788-type polyvinyl alcohol, the hemostatic material is a rigid structure with poor liquid absorption, which shows that quaternized sodium alginate can not only give the material good hemostatic and antibacterial capabilities, but also can be mutually deployed with 1788-type polyvinyl alcohol to achieve the effect of intelligent hemostasis that supports the wound without causing secondary damage to the wound.

[0152] Comparative Example 6

[0153] The difference between this comparative example and Example 1 is that the water washing and alkali neutralization steps are omitted, and the unwashed and alkali-neutralized material is directly used as the hemostatic material.

[0154] This comparative example provides a composite hemostatic material for quickly controlling non-compressive bleeding, and its preparation method specifically comprises the following steps:

[0155] (1) Polyvinyl alcohol type 1788 (BiDe Pharmaceutical, purity 1788), sodium alginate (Shanghai Aladdin Biochemical Technology Co., Ltd., viscosity 200±20 mPa·s), 2,3-epoxypropyltrimethylammonium chloride (Shanghai Aladdin Biochemical Technology Co., Ltd., ≥95%), dextran (Shanghai McLean Biochemical Technology Co., Ltd., average molecular weight 70000), glutaraldehyde 50% (Chengdu Kelong Chemical Co., Ltd., analytical grade), hydrochloric acid (Chengdu Kelong Chemical Co., Ltd., purity 20%) were selected;

[0156] (2) Weighing and preparing the raw materials, the weight ratio of the raw materials is: the weight ratio of 1788 polyvinyl alcohol, sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, dextran, glutaraldehyde, and hydrochloric acid is 15:4.5:7.72:1.01:2.4:5;

[0157] (3) Dissolve sodium alginate in deionized water and stir thoroughly until completely dissolved, add 2,3-epoxypropyltrimethylammonium chloride and stir thoroughly, and place the reaction in a stirrer at 60°C, away from light for 24 hours;

[0158] (4) Adjust the pH value to below 7 and then place at room temperature. Add excess ethanol for precipitation, collect the product and dry it to obtain quaternized sodium alginate;

[0159] (5) Dissolve 1788 polyvinyl alcohol in deionized water and stir at 90 °C at 1200 rpm for 2 hours;

[0160] (6) Take 8.25 ml of hydrochloric acid and add it to a 50 ml volumetric flask. Add deionized water to dilute it to obtain a hydrochloric acid with a mass fraction of 3.3%;

[0161] (7) dissolving dextran in deionized water, adding hydrochloric acid to acidify, adding glutaraldehyde solution to stir and react to obtain dialdehyde-modified polyaldehyde dextran;

[0162] (8) Mix the 1788 polyvinyl alcohol solution and the polyaldehyde dextran solution, and stir at 50°C to mix well;

[0163] (9) Under stirring conditions, add quaternized sodium alginate to the solution (8), and stir at 50° C. at a speed of 1200 rpm for 1 hour;

[0164] (10) Pour the mixed solution into a beaker and let it stand at room temperature, then gradually add hydrochloric acid to acidify it, and stir and foam it at a speed of 1800 rpm for 1.5 hours;

[0165] (11) The foam solution was poured into a mold and vacuum-degassed. After pre-freezing at -35°C for 4 hours, the sample was freeze-dried at -50°C for 48 hours to obtain a composite hemostatic material for rapid control of non-compressive bleeding.

[0166] After testing, the average pore diameter of the material was 32.8 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 4 s, and the contact angle of the material was 32.2° at three seconds. The porosity of the composite hemostatic material was 60.17%, the liquid absorption rate was 2080%, the liquid absorption swelling degree was 6021%, and the compressive strength was 186.34 Kpa. The blood loss of the composite hemostatic material in the rat liver cross incision hemostasis model, the rat liver standard disc loss hemostasis model, and the rat femoral artery transverse incision hemostasis model were 0.62 g, 0.76 g, and 1.5 g, respectively.

[0167] It can be seen from this that if the steps of the present invention are not used and the unwashed and alkali-neutralized material is directly used as a hemostatic material, the unreacted materials in the material will clog the pores and then affect the capillary phenomenon and liquid diffusion. At the same time, the acidic environment will have a great negative impact on the hemostatic performance of the material. The porosity, liquid absorption rate and hydrophilicity of the material are all reduced. The most significant impact is that the liquid absorption expansion degree and hemostatic performance of the material are significantly reduced.

[0168] Comparative Example 7

[0169] The difference between this embodiment and embodiment 1 is that the weight ratio of the prepared materials is: the weight ratio of 1788 type polyvinyl alcohol, sodium alginate, 2,3-epoxypropyltrimethylammonium chloride, dextran (molecular weight 10000), glutaraldehyde, hydrochloric acid, and sodium bicarbonate solution is 15:4.5:7.72:1.01:2.4:5:3.

[0170] After testing, the average pore diameter of the material was 32.62 μm at a scale of 500 μm. The residence time of the droplet on the surface of the composite hemostatic material was 4 s, and the contact angle of the material was 59.59° at three seconds. The porosity of the composite hemostatic material was 86.48%, the liquid absorption rate was 3521%, the liquid absorption expansion was 5692%, and the compressive strength was 131.4 Kpa.

[0171] It can be seen that in Example 1, by increasing the molecular weight of the aldehyde-deoxyglucan cross-linking agent, the porosity and liquid absorption rate of the material did not change much, but the liquid absorption swelling degree and hydrophilicity were significantly improved. The molecular weight of the cross-linking agent has a direct impact on the hydrophilicity and liquid absorption swelling degree of the composite hemostatic material. By selecting the molecular weight of the aldehyde-deoxyglucan cross-linking agent in the scheme of the present invention, the liquid absorption swelling degree and hydrophilicity of the material can be significantly enhanced.

[0172] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite hemostatic material for rapidly controlling non-compressive bleeding, characterized in that: The following steps are involved: S1, mixing sodium alginate, 2,3-epoxypropyltrimethylammonium chloride and deionized water to perform a quaternization reaction, and then adjusting the pH to obtain quaternized sodium alginate; S2, dissolving 1788 type polyvinyl alcohol in deionized water, and then heating and stirring to obtain 1788 type polyvinyl alcohol aqueous solution; S3, acidifying the dextran aqueous solution, and then adding an aldehyde-modifying agent to carry out a modification reaction to obtain an aldehyde-modified dextran solution; S4, adding the aldehyde-modified dextran solution to the 1788-type polyvinyl alcohol aqueous solution, and then adding quaternized sodium alginate to obtain a mixed solution; S5, stirring and foaming, vacuum degassing and freeze-drying the mixed solution in sequence to obtain freeze-dried aerogel; S6, washing the freeze-dried aerogel in sequence, adjusting the pH, and freeze-drying to obtain a composite hemostatic material; The aldehyde modification agent comprises at least one of glutaraldehyde and glyoxal; The mass ratio of the dextran to the aldehyde modification agent is (0.5-3.5):(0.5-1.6).

2. The method for preparing a composite hemostatic material for rapidly controlling non-compressive bleeding according to claim 1, characterized in that: In step S1, the mass ratio of the sodium alginate to the 2,3-epoxypropyltrimethylammonium chloride is (2-8):(3-8).

3. The method for preparing a composite hemostatic material for rapidly controlling non-compressive bleeding according to claim 1, characterized in that: In step S1, the pH value is ≤7.

4. The method for preparing a composite hemostatic material for rapidly controlling non-compressive bleeding according to claim 1, characterized in that: In step S6, the pH value is 7-8.

5. The method for preparing a composite hemostatic material for rapidly controlling non-compressive bleeding according to claim 1, characterized in that: In step S3, the molecular weight of glucose in the dextran aqueous solution is 60,000-80,000.

6. The method for preparing a composite hemostatic material for rapidly controlling non-compressive bleeding according to claim 1, characterized in that: In step S3, the acidification treatment uses hydrochloric acid with a mass fraction of 3.3%.

7. The method for preparing a composite hemostatic material for rapidly controlling non-compressive bleeding according to claim 1, characterized in that: In step S5, the first stage of freeze drying has a processing temperature of -35 to -20°C and a processing time of 2 to 4 hours; the second stage has a processing temperature of -50°C to 0°C and a processing time of 24 to 48 hours.

8. A composite hemostatic material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The composite hemostatic material is composed of the following chemical components in parts by weight: 1 to 10 parts of quaternized sodium alginate, 10 to 15 parts of 1788 type polyvinyl alcohol, and 0.1 to 5 parts of aldehyde-modified dextran.

Citation Information

Patent Citations

  • Antibacterial absorbable nasal cavity hemostatic sponge as well as preparation method and application thereof

    CN115300665A

  • Polysaccharide crosslinking based quick chitosan hemostatic cotton

    CN105477679A

  • Method for preparing high-elasticity high-absorbency hemostatic and bacteriostatic expansive sponge

    CN105816909A

  • Antibacterial modified sodium alginate aerogel hemostatic dressing and preparation method thereof

    CN118806980A